Implementation of ICD-10 Codefication Precision in Diagnosis of Febric Observation of Inpatient Patients (Case Study of Febric Observation Diagnosis in Kanjuruhan Hospital, Malang, Indonesia) - Sri Erna Utami; Ana Sugiati (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2020)
A medical record is a file containing records and documents about the patient's identity, examination, treatment,actions and other services provided to the patient at the health care facility. In principle the contents of themedical record are the property of the patient, while the medical record file (physically) belongs to a hospital orhealth institution. The provision of a good medical record system, one of which must be supported by theaccuracy of ICD-10 verification. the accuracy of codification is very important for hospital management.Factors determining the accuracy of the use of ICD-10 are the diagnosis of disease by the physician and thediagnosis of diagnosis by the medical recorder. Another factor that can lead to inaccuracy is that doctors oftenonly focus on the examination, management and evaluation of the patients they care for. Implementation ofICD-10 coding accuracy on diagnosis of inpatient febrile observation patients at RSUD Kanjuruhan Kepanjenon 50 in-patient medical record documents from August to November 2016. Correct codification of 5 files with10% percentage, incorrect codefication of 40 files with percentage 80% and unfilled codefication 5 files withpercentage 10%. and for patients treated for 2 days the percentage is 8%, the percentage of 3 days is 10%, thepercentage of 4 days is 34%, the percentage of 5 days is 32%, the percentage of 6 days is 10%, the percentage of7 days is 4%, and the percentage is 9 days is 1%. So for the average patient AVLOS patients febrile observationis 4hari. and supported from laboratory result hence normal patient is 33 with percentage 66% and result oflaboratory of abnormal patient is 17 with percentage 34%. It is desirable, the doctor to be able to determine thefinal diagnosis or primary diagnosis because under any circumstances the main diagnosis should be establishedespecially on the final examination. Because in this case, the diagnosis at the end of the examination affects therates and actions given to the patient.Keywords : Febric Observation Diagnosis, implementation, ICD-9 CM, ICD-10